The Morphological and Functional Properties of Lactiplantibacillus plantarum B411 Subjected to Acid, Bile and Heat Multi-Stress Adaptation Process and Subsequent Long-Term Freezing - Thobeka N. Dlangalala; Moloko G. Mathipa-Mdakane; Mapitsi S. Thantsha (Microbiology Research, 2022)
The preadaptation of probiotics to sub-lethal levels of multiple stress factors boosts their survival and stability. However, little is known about how long-term cold storage affects the properties of such preadapted probiotics. This study examined the impact of long-term freezing on structural and functional properties of multi-stress (acid, bile and heat) adapted Lactiplantibacillus plantarum B411. Cell morphology was investigated using scanning electron microscopy, and then their selected functional (bile salt hydrolase (BSH) activity, surface hydrophobicity, auto-aggregative and antimicrobial) properties were evaluated. Furthermore, the survival of L. plantarum B411 cells in yoghurt and juices during storage and under simulated gastrointestinal (GIT) conditions was evaluated. Long-term freezing negatively affected the morphology, auto-aggregation ability, BSH and antimicrobial activities of L. plantarum B411. The viability of freshly adapted and old adapted L. plantarum B411 cells in foods was similar. Under simulated GIT conditions, the viability of the stress adapted cells from the freezer diminished more than that of freshly adapted cells. Prolonged freezing compromised some functional properties of stress adapted cells and their stability under simulated GIT conditions. Care should thus be taken to ensure that a method used to preserve stress adapted cells does not cause them to lose beneficial properties, nor revert to their pre-adaptation status.